2013
DOI: 10.1111/j.1559-8918.2013.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing anthropological reflection within an energy company

Abstract: THE PRIVATE ENERGY USER CHALLENGEGovernments and energy companies are currently developing alternative electricity smart grid solutions to address energy independencies, reliability and issues of sustainability (Massoud and Wollenberg 2005, Gellings 2009, Lin, Yang and Shyua 2013. These developments will lead to a disruption of the continuous evolution of energy use practices both in private households and in energy production companies (Farhangi 2010, Lin, Yang andShyua 2013). The Danish government has deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Here it is important to remember emphasis is placed upon an understanding of human behaviour based on behavioural psychology. Similar conceptions are reported from engineering practices concerned with users within the energy sector (Løgstrup et al, 2013).…”
Section: Challenging Model Based Research Practicessupporting
confidence: 72%
“…Here it is important to remember emphasis is placed upon an understanding of human behaviour based on behavioural psychology. Similar conceptions are reported from engineering practices concerned with users within the energy sector (Løgstrup et al, 2013).…”
Section: Challenging Model Based Research Practicessupporting
confidence: 72%
“…Other studies have found that family members can get in the way of flexing energy demand, in particular where the husband or father of the household consents, but their wives and children undermine their efforts or come into conflict with the strategies they use [36].…”
Section: Respondersmentioning
confidence: 99%
“…Moreover, it is not obvious whether companies in the electricity market would welcome user innovations, as resistance to innovation within corporations is a well‐known phenomenon (Lilien et al , ), and energy companies have been found to be particularly hesitant about value cocreation together with consumers (Bonnemaizon and Batat, ; Løgstrup et al , ). Finally, it is not self‐evident that lead users can contribute to innovation involving social rather than private benefits (Schaltegger and Wagner, ) as is the case in the development of a smart, low‐carbon energy system.…”
Section: Conceptual Framework: Applying Lead User Theory To “Smart” Ementioning
confidence: 99%